Europium and erbium co-doped yttria-stabilized zirconia as a potential dual-sensor for simultaneous oxygen partial pressure and temperature measurements. Issue 7 (1st April 2023) - Yang, Lixia; Fu, Yating; Cheng, Weilun; Peng, Di; Chen, Zhaofeng; Luo, Lirong; Zhao, Xiaofeng; Liu, Yingzheng; Kou, Zongde
Abstract: In this study, the phosphorescence properties of Eu 3+ and Er 3+ co-doped yttria stabilized zirconia (YSZ: Eu 3+, Er 3+ ) as a function of oxygen partial pressure and temperature are investigated to explore the possibility of using this phosphor for pressure and temperature measurements at elevated temperature (up to 600 °C). The YSZ: Eu 3+, Er 3+ phosphors have a fixed Eu 3+ concentration (1 mol%) and a varied Er 3+ concentration (0.5–5 mol%). The phosphorescence intensity and lifetime of Eu 3+ bands are sensitive to both oxygen partial pressure and temperature when temperature exceeds 400 °C. This oxygen/pressure sensitivity is related to the oxygen vacancy-induced non-radiative decay through charge transfer state (CTS), and is inversely correlated with Er 3+ concentration. In contrast, the phosphorescence intensity and lifetime of Er 3+ bands are temperature-sensitive but oxygen-insensitive, which is related to the dominant oxygen-independent 4 S3/2  →  2 H11/2 transition. Accordingly, two measurement strategies are proposed including an intensity ratio method and a lifetime method. The intensity ratio of the oxygen-sensitive Eu 3+ bands and the oxygen-insensitive Er 3+ reference bands is capable of 2D pressure measurement using a dual-camera system. But temperature-induced errors exist due to the temperature-sensitivity of intensity ratio. Simultaneous pressure and temperature measurements (point by point) can be achieved utilizing two PMTs that record the lifetimes of Eu 3+ and Er 3+, respectively. This method can resolve the issue of temperature sensitivity of Eu 3+ and accurately correct the temperature-induced errors. The YSZ: Eu, Er phosphors show great potential for applications in high-temperature environment where the existing organic PSPs and TSPs cannot survive.